Effects of biochar application with fertilizer on soil microbial biomass and greenhouse gas emissions in a peanut cropping system. Issue 1 (2nd January 2021) - Tan, Guangcai; Wang, Hongyuan; Xu, Nan; Junaid, Muhammad; Liu, Hongbin; Zhai, Limei
ABSTRACT: This study investigated the effects of biochar application with organic or mineral fertilizers on soil microbial biomass, and associated emissions of CO2 and CH4 under field settings planted with peanut. The results indicated that physicochemical properties of soil were improved under biochar application. Soil microbial biomass carbon (MBC) was significantly increased with the application of biochar plus organic fertilizer compared to that of organic fertilizer only, but no significant difference of MBC was found between the treatment under biochar application plus mineral fertilizer and that under mineral fertilizer only. Biochar application did not affect the amount of microbial biomass nitrogen (MBN) with either mineral or organic fertilizer. The cumulative CO2 emission did not change under biochar application, while the cumulative CH4 emission was significantly decreased ( p < 0.05) by 68.67% on average with the application of organic fertilizer plus biochar compared to that of organic fertilizer only. When biochar was applied in combination with either mineral or organic fertilizer, both the net global warming potential (GWP) and the greenhouse gas intensity (GHGI) were significantly decreased compared to that without biochar amendment. In all, biochar can improve soil quality, and enhance soil carbon sequestration as well as peanut yields. GRAPHICAL ABSTRACT: UF0001